Catastrophic Gastrointestinal Bleeding: Always Consider Meckel’s Diverticulum - Filipa Pedro; Joana Romano; Marta Rebelo; Rogério Matias; Eduarda Carmo (European Journal of Case Reports in Internal Medicine, 2019)
Meckel’s diverticulum, a congenital malformation of the gastrointestinal tract, is asymptomatic in the majority of patients but can be associated with some complications. Gastrointestinal bleeding is one such complication and is more common in children than in adults. Despite the variety of examinations available, diagnosis can be difficult, especially in older patients, because the sensitivity of examinations decreases with patient age. Here we present the case of a young man with gastrointestinal bleeding in whom a diagnosis of Meckel’s diverticulum was made intra-operatively.